GIANT VIRUSES: ORIGIN, SPREADING, TAXONOMICAL, STRUCTURAL-MORPHOLOGICAL AND MOLECULAR-BIOLOGICAL CHARACTERISTICS - D. K. Lvov; T. E. Sizikova; V. N. Lebedev; S. V. Borisevich (Вопросы вирусологии, 2018)
The brief review is devoted to description of the discovery of giant viruses belonging to the families of Mimiviridae and Marseilleviridae, as well as unassigned genera Pithoviruses, Pandoravirus, and Molliviruses. The review presents issues of their origin, evolution, and molecular-biological characteristics.